The Identification of Risks and its Criticality in the Nigeria Construction Industry - A.C.C. Ezeabasili; N. U. Dim; C.A.C Ezeabasili; J. J. Obiefuna (International Journal of Engineering and Management Research, 2021)
Failure in project delivering can be attributed to many risk events in the Nigerian Construction Industry. This risk could be as a result of the dynamic, sensitivity, and complexity of the construction Industry towards its environment, socio-political, economic, technology, and cultural variables in Nigeria. Nevertheless, the low level of Risk Management in Nigeria construction Industry, and the little understanding and knowledge of the subject by Project Stakeholders prompt this study. A quantitative method of research was carried out, and among the sixty (60) questionnaires administered to clients, consultants, and contractors in the Nigerian construction industry, thirty-one (31) valid responses were obtained. The questionnaires were designed on the twenty (20) types of risks that were identified by construction professionals which were categorized into five namely; Government and Politics; Finance and Economical; Management and Technology; social and Cultural; Natural and Environmental Risks. And, findings made revealed that economic and financial risks surpass all other types in the Nigeria Construction Industry.